Resilience of The Cempaka Cilangkap Cipayung Park Tourism Object Through The Completeness and Quality of Tourism Facilities - Latif, Bagus Syarifuddin; Nugraha, Rizki Nurul (Westscience Press, 2024)
This research is entitled